Effect of nozzle diameter variation on flame height and combustion residue in a household scale incinerator burner - Endi Novrizal; Adhes Gamayel; Mohamad Zaenudin; Anugrah Budi Wicaksono; Alvin Mubarok (LPPMPK- Universitas Muhammadiyah Cileungsi, 2027)
Household waste is one of the main components of household waste in Indonesia, and its growth year-on-year requires solutions for efficient processing in the future through approaches of reduction, reuse and recycling. A possible solution is to reduce waste at household level and is the use of micro-scale incinerators. The efficiency of these systems, however, is very dependent on the combustion properties of the burner. The purpose of this study is to develop a household incineration system and to investigate the variation of nozzle size (2, 3 and 4 mm) on the flame height and combustion residue. 500g of plastic waste and dry leaves were used for each experiment. The results reveal that the nozzle of 2 mm is the most optimized nozzle which achieved mass reduction of 99.46% for plastic waste and 99.64% for dry leaves with a maximum flame height of 27 cm for both the plastic waste and dry leaves. The results show that nozzle diameters have a significant impact on the fuel–air mixing and the velocity of the resulting flow, which results in more complete combustion as evidenced by the level of flame height and the amount of residue. The study suggests that for household incinerator applications the nozzle should be no smaller than 2 mm, and diameters of less than 2 mm should be further investigated as there is a possibility of clogging and back‑pressure.